Importance of Glutamate Dehydrogenase (GDH) in Clostridium difficile Colonization In Vivo - Girinathan, Brintha Parasumanna; Braun, S.; Sirigireddy, Apoorva Reddy Sirigireddy; Lopez, Jose Espinola; Govind, Revathi (My University, 2017)
Clostridium difficile is the principal cause of antibiotic-associated diarrhea. Major metabolic requirements for colonization and expansion of C. difficile after microbiota disturbance have not been fully determined. In this study, we show that glutamate utilization is important for C. difficile to establish itself in the animal gut. When the gluD gene, which codes for glutamate dehydrogenase (GDH), was disrupted, the mutant C. difficile was unable to colonize and cause disease in a hamster model. Further, from the complementation experiment it appears that extracellular GDH may be playing a role in promoting C. difficile colonization and disease progression. Quantification of free amino acids in the hamster gut during C. difficile infection showed that glutamate is among preferred amino acids utilized by C. difficile during its expansion. This study provides evidence of the importance of glutamate metabolism for C. difficile pathogenesis.
Citation: Girinathan, B. P., Braun, S., Sirigireddy, A. R., Lopez, J. E., & Govind, R. (2016). Importance of Glutamate Dehydrogenase (GDH) in Clostridium difficile Colonization In Vivo. Plos One, 11(7), 18. doi:10.1371/journal.pone.0160107
Keywords: Toxin Production; Pseudomembranous Colitis; Bacillus-Subtilis; Metabolism; Virulence; Integration